Elucidation of the photocatalytic removal pathways of humic substances: progress towards mechanistic explanations - Uyguner, Ceyda Senem. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2005., 2005)
The objective of this research was to characterize the spectroscopic properties ofhumic and fulvic acids of different origins as model compounds to represent the naturalorganic matter in aquatic systems. The photocatalytic oxidation of model humic and fulvic acids was carried out using TiO2 Degussa P-25 as the photocatalyst. The degradationkinetics was assessed based on pseudo first order and Langmuir Hinshelwood (L-H)kinetic models. The related data for aquatic and terrestrial humic substances werecomparatively presented in terms of UV-vis parameters such as Color436, Color400, UV365, UV300, UV280, UV254 and total organic carbon (TOC) removal. Furthermore, the molecularand structural characteristics of the humic acid molecule relative to changes duringphotocatalytic oxidation were monitored by spectroscopic techniques.On the basis of their diverse chemical and physical properties such as molecular weight, molecular size, elemental composition and source of origin, substantial differenceswere observed in photocatalytic removal efficiencies of humic and fulvic acids. For all ofthe humic substances, higher removal rates were achieved in terms of UV254 valuescompared to that of Color436. Moreover, humic acids exhibited higher pseudo first order removal rates with respect to that for fulvic acid. The declining trend of the specified UVvisparameters, the related changes in the fluorescence spectra (initial increase of thefluorescence intensities, formation of new fluorophores, shift of the spectra to lowerwavelength region and decline of intensity after long photocatalytic irradiation times), decrease of TOC content during degradation, the spectral changes in FTIR and NMRindicated the oxidative degradation of humic substances.Considering the complexity and polydispersity of the humic macromolecules, theywere fractionated into well defined subcomponents of known molecular sizes usingultrafiltration through membranes in the range of 100-1 kDa. The effect of photocatalyticoxidation on the molecular size fractions of humic substances were also evaluated on acomparative basis by UV-vis and fluorescence spectroscopy. As confirmed by the spectroscopic evaluation of the molecular size distributiondata, photocatalytic degradation of humic acid leads to the formation of lower molecularsize (small fractions) and higher UV-absorbing compounds. For fractions less than 10 kDa,UV254 absorbing moieties in treated humic acid samples become higher than that of rawhumic substances designating the generation of new species during photocatalysis.Based on the comparison between the synchronous scan fluorescence spectra ofthe molecular size fractions of raw and oxidized humic substances, it could be concludedthat oxidative cleavage of the molecule leads to a blue shift of the spectra which isindicative to the formation of new fluorophores in each size fraction. It is assumed thatoxidative degradation of the macromolecule occurs through an unselective pathway, by thereaction of .OH radicals with the various moieties within each fraction.
Keywords: Humus -- Environmental aspects.; Humic acid.; Water -- Purification -- Photocatalysis.